An Epidemiological Study Of Hypertension Among Residents In Pune - Deswal B.S; Satyamoorthy T.S; Dutta P.K; Ganguly S.S (Wolters Kluwer Medknow Publications, 1991)
An epidemiological study was undertaken to determine the prevalence of hypertension. A case control study to examine the association of certain risk factors in the subsequent development of the disease was simultaneously done. Following screening procedures as per the WHO criteria, 134 of 1818 adults residing in a semi-urban population in Pune were found to be hypertensive giving a prevalence of 7%. A total number of 96 new cases and an equal number of control subjects were studied under matched control design. Few of the important risk factors like obesity, sedentary habits, occupation, alcohol consumption, stress, anxiety and hereditary factors were found to have a significant role in subsequent development of disease.